Extensão da ferramenta MVCASE com serviços remotos de armazenamento e busca de artefatos de software - Lucrédio, Daniel (2005)
Software reuse aims to increase productivity and to decrease time-to-market, through work optimization and avoiding effort duplication. In this context, two areas arise: Software Components and Computer-Aided Software Engineering (CASE). The Component-Based Development approach aims to offer ways to build more reusable software. The use of CASE seeks to reduce effort, by delegating part of the tasks to be performed by the computer, and to improve quality, by helping the Software Engineer to perform some tasks. Combining the ideas of software components and CASE, this dissertation presents an extension of MVCASE tool, an academic tool developed in UFSCar - Federal University of São Carlos, with remote services for storage and search for software artifacts, aiming to improve productivity and to reduce time and costs in software development.